Maternal Anxiety with Infant Pain During Immunization - Halimah, Halimah; Yan, Loriza Sativa; Renylda, Reta (Jurnal Ilmiah Kesehatan (JIKA), 2024)
Maternal and child health is still the target of health development programs in Indonesia. Immunization is important to prevent children from getting sick or even dying from certain diseases. The procedure for giving immunizations, most of which are by injection, is one of the reasons parents delay or even don't bring their children to be immunized because they can't bear to see their children cry. This study aimed to see the relationship between maternal anxiety and the pain felt by infant during immunization. This research method was a descriptive study with cross-sectional design and consecutive sampling technique. The study was conducted at the Pakuan Baru Health Center Jambi on 115 respondents consisting of mothers and infant (0-12 months) who received injection-type immunization. Maternal anxiety was measured using the DASS-21 questionnaire and the infant's pain was observed with the FLACC behavioral tool. The results of Spearman's rho analysis obtained a p-value of 0,0001 (p-value<0,05), which means that there is a significant relationship between maternal anxiety and the pain felt by infant during immunization with a strong correlation (r=0,625). We hope that the results of this study become a concern for health workers, to reduce maternal anxiety to decreases infant's pain and in the end can increase immunization coverage which has an impact on improving children's health status.